Small‐scale silvopasture: Addressing urban and peri‐urban livestock challenges in the United States with agroforestry practices. Issue 1 (4th February 2022) - Conway, Ashley; Nieman, Christine
Abstract: The growing urban and peri‐urban populations around the world creates strain on food and environmental security. Alleviation of these stressors may be possible by enhancing regional food production and ecosystem services provided by urban and peri‐urban agriculture (UPA). Despite the growing popularity of UPA in the United States, incorporating livestock in these settings is challenging. A review of the literature identified three key barriers to adoption of urban and peri‐urban livestock keeping that have the potential to be ameliorated using agroforestry practices to facilitate integration: animal feed resources, water quality and nutrient cycling, and use of sites contaminated with heavy metals. A discussion focused on the solutions to those barriers resulted in two theoretical silvopasture systems; we propose one for the urban setting and another for the peri‐urban setting. We have determined small‐scale livestock keeping provides a potential strategy to meet the demands of growing urban and peri‐urban environments, but sustainable and effective integration of livestock under these conditions must be considered to mitigate environmental risks associated with urban livestock keeping. Urban silvopasture has the potential to enhance specialty crop and niche food production in these environments. Future research should seek to better understand small‐scale silvopasture at the whole‐system level in a variety of resource contexts and with local species and practices. Core Ideas: Increasing urbanization necessitates innovative and adaptive food production systems. Urban agriculture and livestock keeping in the United States face several challenges for effective implementation. Common urban agriculture and livestock challenges may be mitigated via silvopasture integration. The capacity of silvopasture to provide co‐benefits and mitigate challenges is unknown. Two system models for urban and peri‐urban silvopasture are proposed to facilitate validation of potential